Minimal Residual Disease Detection by Next-Generation Sequencing in Multiple Myeloma: A Comparison With Real-Time Quantitative PCR - Yao, Qiumei; Bai, Yinlei; Kumar, Shaji; Au, Elaine; Orfao, Alberto; Chim, Chor Sang (Frontiers in Oncology, 2021)
Here we compared clonotype identification by allele-specific oligonucleotide real-time quantitative-PCR (ASO RQ-PCR) and next-generation sequencing (NGS) in 80 multiple myeloma patients. ASO RQ-PCR was applicable in 49/55 (89%) and NGS in 62/78 (80%). Clonotypes identified by both methods were identical in 33/35 (94%). Sensitivity of 10-5 was confirmed in 28/29 (96%) by NGS while sensitivity of RQ-PCR was 10-5 in 7 (24%), 5x10-5 in 15 (52%), and 10-4 in 7 (24%). Among 14 samples quantifiable by ASO RQ-PCR, NGS yielded comparable results in 12 (86%). Applicability of NGS can be improved if immunoglobulin heavy-chain incomplete DJ primers are included.